Analysis Human Resources Development in Province Of Nusa Tenggara Timur From 2013-2015 - I Wayan Sunarya (STIM LASHARAN JAYA MAKASSAR, 2017)
This study aims to analyze the influence of Life Expectancy (LE), Expected Years of Schooling (EYS), Mean Years of Schooling (MYS), Adjusted per Capita Expenditure (ACE) to Human Development Index (HDI) in province of Nusa Tenggara Timur from 2013 until 2015. Secondary data, from the websiteCentral Bureau Statistics province Nusa Tenggara Timur that is http://ntt.bps.go.id and article entitled “Nusa Tenggara Timur in Figures”, which is published once a year. This study implemented data panel with Fixed Effect Model (FEM) method of Generalized Least Square (GLS). The results show that the Expected Years of Scooling (EYS) and Mean Years of Schooling (MYS) has positive and significant effect to Human Development Index (HDI) in province Nusa Tenggara Timur from 2013 until 2015. However, Life Expectancy (LE) and Adjusted per Capita Expenditure (ACE) doesn’t significant effect to Human Development Index (HDI) in province of Nusa Tenggara Timur from 2013 until 2015.